Balance Score Card and Business Performance: A Comparative Study of State and Private Sector Banks in Eastern Provinces of Sri Lanka - Haleem, H.M.M.; Muraleetharan, P. (Faculty of Management and Commerce, 2016)
The balance score card (BSC) is a management system that maps an organization’s strategic objectives into performance with four perspectives such as financial, internal business perspectives, customers, and learning and growth which provide relevant feedback as to how well the strategic plan is executing so that adjustment can be made if necessary. The score card itself is essentially a performance measurement frame work with two key objectives; converting strategy into specific goals for different sections of the organization, and communicating that strategy to all parts of the organization. Hence the associations between four perspectives in balance score card and performance should be examined. Various studies have been done on the above theme, but no enough studies have been conducted in Sri Lankan context, especially in banking sector. Thus the present study is initiated on “Balance score Card and business performance as a comparative study of state and private sector banking Organizations in Srilanka “with a samples of 143 respondents in 16 banking organizations in eastern provinces. The results from the operational hypotheses indicates that total perspectives (CP, IBP, LGP, and FP) have a significant relationship with business performance which means, as the total perspectives increase business performance increases in state banks and private banks. Whereas learning growth perspectives and customer perspectives significantly contributes to total perspectives in both banks are important contributors to positive Business performance, specially learning growth perspectives are significantly impact on state banks. But the private banks customer perspective is mostly impact on business performance.
Keywords: Balance score card; financial perspectives; internal business perspectives; Customer perspective; Learning and growth perspectives; business performance